Analisis Akuntansi untuk Transaksi Mata Uang Asing pada PT. Sumi Indo Kabel Tbk (Jurnal Kendali Akuntansi, 2024)
This research is motivated by the need for PT Sumi Indo Kabel Tbk to manage foreign currency transactions in line with the increase in international trade and exchange rate fluctuations. Foreign currency transactions can affect the company's financial statements, especially in the recognition of profit or loss due to changes in exchange rates. The purpose of this study is to analyze the application of foreign currency transaction accounting at PT Sumi Indo Kabel Tbk based on Statement of Financial Accounting Standards (PSAK) 221 on the Effect of Changes in Foreign Exchange Rates. The research method used is descriptive quantitative, using secondary data obtained from the company's annual financial statements. The results showed that PT Sumi Indo Kabel Tbk has implemented PSAK 221 properly, recorded foreign currency transactions at the prevailing exchange rate and recognized the exchange difference in the income statement. However, the company still faces the risk of significant exchange rate fluctuations, which requires a more comprehensive risk management strategy. The conclusion of this study is that consistent implementation of PSAK 221 can help companies improve the transparency of financial statements and reduce the negative impact of exchange rate fluctuations on financial performance..